Confronting the cataracts of whiteness to see the invisible: reflections on the transmission and reception of the Bible in post-apartheid South Africa - J. Kok (Acta Theologica)
The goal of this article is to draw on some of the latest insights in biblical studies on the challenges posed to the reflection, transmission, and reception of the Bible with relevance to a post-apartheid South African context. The author engages with prominent figures in the field of Biblical Studies and critical race theory such as David Horrell, in order to address the issue of whiteness and its impact on marginalisation. The aim is to foster a deeper understanding of the ways in which certain voices have been rendered invisible and to continue to question and challenge these dynamics. This paper delves into the interpretation of the Bible in Africa, using the perspectives of scholars such as Thomas Wartenberg in conjunction with the ideas of Charles W. Mills, W. Jennings, R. Ellison, and Steven Biko, as well as other notable figures, to critically reflect on the role of biblical scholarship in the process of restoring historically marginalised voices within the context of past injustices.